CONTEXTUALIZACIÓN Y ANÁLISIS TECNOLÓGICO DE LAS PIEZAS DE METAL DEL SITIO ARQUEOLÓGICO ANCÓN - Castro de la Mata, Pamela (2009)
Ancon is one of the archaeological sites in the central coast, where national and international teams have excavated since 1875. As a result of these excavations significant and substantial amount of material evidences over 2,000 years of occupation. This research provides a documentary and analytical study of the metal objects recovered from Ancon that are currently part of the collections of the National Museum of Archeology, Anthropology, and History of Peru (MNAAHP). The study includes the use of ornaments and functional objects as offerings in tombs which has contributed to develop funerary patterns of the use of metals in mummy bundles. The metal artifacts found at Ancon vary in technological styles and types. Its characterization was performed using electron microscopy and X-rays, which allowed us to identify the composition of the metals present. Among the metals found at the site the use of gold alloyed with silver and copper, and copper and/or silver are predominant. This identification provides an interesting insight of the techniques used on the Central Coast.